2020
DOI: 10.3390/ijms21031143
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase and Septic Conditions Disrupt Sphingolipid Homeostasis in Murine Brain Capillaries In Vivo and Immortalized Human Brain Endothelial Cells In Vitro

Abstract: During inflammation, activated leukocytes release cytotoxic mediators that compromise blood–brain barrier (BBB) function. Under inflammatory conditions, myeloperoxidase (MPO) is critically involved in inflicting BBB damage. We used genetic and pharmacological approaches to investigate whether MPO induces aberrant lipid homeostasis at the BBB in a murine endotoxemia model. To corroborate findings in a human system we studied the impact of sera from sepsis and non-sepsis patients on brain endothelial cells (hCME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
(87 reference statements)
1
8
0
Order By: Relevance
“…TNF‐α is a multifunctional cytokine that follows TLR‐4 activation and causes subsequent upregulation of other cytokines in the proinflammatory cascade, e.g. interleukins, adhesion molecules, and MPO 20,41‐43 . Overall, our findings favour the idea that implicates calcineurin inhibition in the heightened inflammatory and nephrotoxic effects of endotoxaemia upon concurrent exposure to cyclosporine or tacrolimus.…”
Section: Discussionsupporting
confidence: 57%
“…TNF‐α is a multifunctional cytokine that follows TLR‐4 activation and causes subsequent upregulation of other cytokines in the proinflammatory cascade, e.g. interleukins, adhesion molecules, and MPO 20,41‐43 . Overall, our findings favour the idea that implicates calcineurin inhibition in the heightened inflammatory and nephrotoxic effects of endotoxaemia upon concurrent exposure to cyclosporine or tacrolimus.…”
Section: Discussionsupporting
confidence: 57%
“…Treating endothelial cells with serum from septic patients resulted in endothelial cell SM loss accompanied by a sharp and rapid production of Cer, which then is further metabolized to glycosylated ceramides (122). However, these results were not observed by Sattler et al, who observed decreases in brain endothelial cell levels of Cer and an associated loss of barrier function after treatment with septic patient serum (123). Decreased S1P levels in human sepsis is likely the result of reduced sphingosine kinase (Sphk1 and J o u r n a l P r e -p r o o f Sphk2) activity (112).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 74%
“…Depending on the origin of the cell types of interest, the composition of ECM incorporated into the models should also be considered. BM coating considerations for endothelial cell phenotypes should be cell type-dependent, as immortalized cell lines have similar phenotypes across different ECM substrates or without coatings [ 270 , 271 , 272 , 273 , 274 , 275 ], primary cells have shown promising results with fibronectin, collagen IV and laminin as the BM [ 231 , 276 ] and iPSC-derived BMECs show physiological behavior when cultured with collagen IV/fibronectin coatings, Matrigel ® , and possibly laminin-221 [ 44 , 279 ]. Any investigators studying barrier function should consider testing an array of BM compositions to find a suitable option for their specific cell source.…”
Section: Discussionmentioning
confidence: 99%
“…Since HCMEC/D3 cells are the most commonly used BMEC cell line, we will focus on coatings compatible with these cells. Given their generally robust phenotype (reviewed in [ 79 ]), most studies that do use a coating for these cells select generic rat-tail collagen-I (10 ug/cm 2 ) [ 272 , 273 , 274 , 275 ] due to its low cost, even though collagen-I is not found in the cerebral microvasculature. Several combinations of coatings that are more physiologically relevant have been tested in an attempt to optimize the barrier formation of HCMEC/D3, with little success.…”
Section: Decision Workflow: Factors To Consider When Selecting a Model Systemmentioning
confidence: 99%